2004
DOI: 10.1191/0961203304lu520oa
|View full text |Cite
|
Sign up to set email alerts
|

Is HLA class II susceptibility to primary antiphospholipid syndrome different from susceptibility to secondary antiphospholipid syndrome?

Abstract: To assess whether the major histocompatibility complex (MHC) profile of patients presenting with primary antiphospholipid syndrome (PAPS) is different from that of patients with secondary antiphospholipid syndrome (SAPS), we studied 123 patients, 34 of whom presented PAPS and 35 SAPS due to systemic lupus erythematosus (SLE), 54 SLE patients without antiphospholipid syndrome (APS), and 166 controls. HLA-DRB1 and DQB1 alleles were typed using amplified DNA hybridized with sequence-specific primers. Compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…19,21,22 Additional studies will be necessary to determine how the Val/Leu 247 polymorphism in the β2-GPI gene could influence the development of APS and the production of anti-β2-GPI antibodies. The involvement of other β2-GPI polymorphisms, HLA class II genes, 23 and environmental variables also needs to be considered. 24,25…”
Section: Discussionmentioning
confidence: 99%
“…19,21,22 Additional studies will be necessary to determine how the Val/Leu 247 polymorphism in the β2-GPI gene could influence the development of APS and the production of anti-β2-GPI antibodies. The involvement of other β2-GPI polymorphisms, HLA class II genes, 23 and environmental variables also needs to be considered. 24,25…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies will be necessary to distinguish how and which domain of β 2 GPI the anti‐β 2 GPI antibodies are directed against, how β 2 GPI polymorphism influences the production of anti‐β 2 GPI antibodies and what other β 2 GPI polymorphisms, human leukocyte antigen class genes and environmental variables should also be taken into account when considering anti‐β 2 GPI antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative results showed that each domain of b 2 GPI has been indicated as the location where anti-b 2 GPI antibodies may bind, and not all anti-b 2 GPI IgG antibodies have the same epitope specificity. Additional studies will be necessary to distinguish how and which domain of b 2 GPI the anti-b 2 GPI antibodies are directed against, how b 2 GPI polymorphism influences the production of anti-b 2 GPI antibodies and what other b 2 GPI polymorphisms, human leukocyte antigen class genes [17] and environmental variables should also be taken into account when considering anti-b 2 GPI antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…These studied have not compared PAPS and SAPS. In Brazil, a genetically diverse population, Freitas et al [21] studies 34 patients with PAPS, 35 patients with SAPS with SLE, 54 SLE patients without APS, and 166 controls. They found that HLA-DRB1*03 alleles were increased in SAPS and in SLE patients as a whole but not in PAPS or controls.…”
Section: Genetic Associationsmentioning
confidence: 99%